Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif Melalui Inovasi Produk Badeg Cincau di Desa Sokawera Kecamatan Cilongok Kabupaten Banyumas - Zaula Rizqi Atika; Chamid Sutikno; Shadu Satwika Wijaya (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Empowerment is one way to create an independent and competitive community and can meet their life needs, especially in the economic aspec of the community. The Implementation of this empowerment is the main step in developing the capacity and quality of the skills and abilities that are still few. This is in line with many creative economy products in the community which are still in the development stage and are still late with other products. The existence of this creative economy product has more potential that is managed well and has broad benefits by the community. For that, the government as the main party that plays a role in empowering community resoursce in general to continue to encoutage the improvement of the creative economy in the community.one of the creative economy products is Badeg cincau which is located in Sokawera village, Cilongok Subdistrict, Banyumas District which is managed and produced by the surrounding community. However, due to limited resources, the community has not been able to maximize the production of Badeg Cincau in a modern and broad way. Based of this, the presence of community service regarding” Community empowerment based on creative economy through innovation of badeg cincau products in Sokawera Village, Cillongok SubDistrict, Banyumas District.